Military engineers and the development of the early-modern European state - Lenman, Bruce (Dundee University Press, 2013)
An unique insight into the role of the Early-Modern European military engineers in the construction and empowerment of sovereign authority, both in European kingdoms and republics and in the vast overseas dominions some of them acquired through the Expansion of Europe.